Enhanced interfacial adhesion in carbon fiber/poly (acrylonitrile‐butadiene‐styrene) composite through fiber surface treatment by an emulsion sizing. Issue 10 (12th April 2015) - Ma, Xiaolong; Ge, Heyi; Liu, Huashi
Abstract : To improve the interfacial adhesion between carbon fiber (CF) and poly(acrylonitrile‐butadiene‐styrene) (ABS) thermoplastic, an emulsion sizing whose film former was a terpolymer N ‐phenylmaleimide‐styrene‐maleic anhydride (NSM)/ABS mixture was prepared. NSM, an efficient heat‐resistant modifier for ABS, could make the film former possess a superior heat resistance, which helped the sizing layer maintain integrity during the preparation of CF/ABS composite. Moreover, differential scanning calorimetry (DSC) results demonstrated that the glass transition temperature ( T g ) of the NSM modified ABS achieved an improvement of 25.3°C. Particle size and distribution of the sizing agent were investigated to evaluate its stability. The FTIR spectrum obtained demonstrated that the chemical compositions of the sized CF got greatly changed and numerous functional groups appeared on sized CF. Abrasion resistance and fluffs of CF were tested and the results indicated that the sized CF obtained an appreciable enhancement in handleability. Interlaminar shear strength (ILSS) results revealed, after sizing, that the ILSS enhanced by 26.6%, due to the inserted sizing layer between CF and ABS matrix. POLYM. COMPOS., 37:2940–2949, 2016. © 2015 Society of Plastics Engineers